Birds That Don't Exist: Niche Pre‐Emption as a Constraint on Morphological Evolution in the Passeroidea - Stephanie Y. Chia; Anshuman Swain; Nathaniel Josephs; Lizhen Lin; William F. Fagan (Ecology Letters, 2026)
Understanding why some viable body forms never evolve can reveal how ecological and evolutionary forces shape biodiversity. We investigate this question in the Passeroidea, a large group of songbirds, by analysing their morphological trait space using topological data analysis and ancestral state reconstruction. We identify a persistent morphological gap densely surrounded by extant species but unoccupied throughout passeroid diversification. The gap patterns deviate from stochastic expectations and show no evidence of past occupation, rendering undirected trait evolution and extinction unlikely. Similar morphologies exist in other bird lineages, ruling out intrinsic constraints or niche absence. Geographic distributions and traits of passeroids versus non‐passeroid gap occupants point to competitive exclusion as the plausible explanation: early‐colonising territorial specialists outside the Passeroidea may have preemptively occupied key habitats, limiting evolutionary opportunities for later‐arriving lineages. We demonstrate how historical contingency can shape macroevolutionary outcomes and introduce a generalizable framework for investigating structural gaps in trait evolution.